2022
DOI: 10.21203/rs.3.rs-1993286/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Basic Developmental Characteristics of the Fall Armyworm, Spodoptera Fruiperda (J.E. Smith) (Lepidoptera: Noctuidae) Reared Under Laboratory Conditions

Abstract: The life cycle of the invasive alien insect pest, Fall armyworm (FAW), was studied using a colony established from field-collected larvae. Eggs, neonate larvae and newly emerged adult moths were used in the experiments to determine the basic biology of the FAW. Matured females laid up to 1184 eggs with mean fecundity of 469 ± 22 eggs per female. Incubation period of eggs and percentage hatchability were 2–3 days and 80–87% respectively. Larval lengths from first to sixth instar were 4.63, 6.60, 9.76, 15.86, 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Sonali Deole and Nandita Paul [19] reported the length and width of sixth instar larva were 32-35 and 6.01 mm, respectively. Dinnah Marri et al [18] reported the larval weight of 0.067 gm which supports the present findings.…”
Section: Sixth Instarsupporting
confidence: 91%
See 2 more Smart Citations
“…Sonali Deole and Nandita Paul [19] reported the length and width of sixth instar larva were 32-35 and 6.01 mm, respectively. Dinnah Marri et al [18] reported the larval weight of 0.067 gm which supports the present findings.…”
Section: Sixth Instarsupporting
confidence: 91%
“…Reddy et al [16] observed the mean length and width of 3.32±0.48 and 0.69±0.04 mm, respectively. Dinah Marri et al [18] observed the average weight of second instar larvae was 0.019 gm.…”
Section: Second Instarmentioning
confidence: 97%
See 1 more Smart Citation